A brief reconnaissance of thee Chiapas Municipalities - Peterson, Fredrick A.; Clark, John E. (México : New world Archaeological foundation brigham young University, 2014)
Preparing for the research -- Background to the servey and Región -- Reconnaissance in the Ocozocoautla, Jiquipilas, and Cintalapa municipalities -- Annual report 1958: reconnaissance of the la venta and cintalapa rivers -- A short trip along the la venta river canyon, 1959 -- A census of western Chiapas sites -- Notes on the culture history of western Chiapas.
As they would say in southern México, the research published posthumously here is an example of "peor es nada" "something is better than nothing...
Incluye bibligrafía
General
Keywords: Antropología histórica -- México -- 1958- -- Chiapas-México